PEMBERDAYAAN UMKM DI INDONESIA MELALUI GERAKAN LITERASI : ANALISIS RANTAI TAK PUTUS KARYA DEE LESTARI - Umi Hani’ah; Alfina Syahara Putri; Eva Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to assess the level of empowerment of Micro, Small and Medium Enterprises (MSMEs) in the Waru and Tapin districts by the Dharma Bakti Astra Foundation (YDBA). The research method used is descriptive qualitative by means of literacy and analysis of a related buku entitled Rantai Tak Putus. The main topic of discussion is about the 5R guidelines (Concise, Neat, Clean, Careful and Diligent) developed for the empowerment of MSME actors. The result of the discussion is that the empowerment program by Yayasan Dharma Bakti Astra is carried out by looking at the aspects of resources, production, and marketing. This has proven to be effective in controlling the activities of MSMEs provided by the Dharma Bakti Astra Foundation.